Outcomes of surgically treated infective endocarditis in a Western Australian population - Aditya Eranki; Ashley R. Wilson-Smith; Umar Ali; Akshat Saxena; Eric Slimani (Journal of Cardiothoracic Surgery, 2021)
Abstract Background Infective endocarditis is a disease that carries high morbidity and mortality. The primary endpoint of this study is to assess factors associated with in-hospital mortality in patients undergoing valvular surgery for infective endocarditis. The secondary endpoint of this study is to assess the incidence of post-operative stroke, renal failure, complete heart block and recurrence. Methods Between the years of 2015 to 2019, a total of 89 patients underwent surgery for infective endocarditis at Fiona Stanley Hospital, Western Australia. Data was collected from the Australia and New Zealand Cardiac Surgery Database from 2015 to 2019 as well as patients electronic medical record. A number of preoperative and perioperative factors were assessed in relation to patient mortality and morbidity. Univariate and multivariate logistical regression analysis was done to assess for the association between factors and in-hospital morbidity and mortality. Results A total of 89 patients underwent surgery for infective endocarditis from 2015 to 2019, affecting a total of 101 valves. The mean age of patients was 53.7 ± 16.5. A total of 79 patients had a positive blood culture pre-operatively, with Staphylococcus Aureus being the most frequently cultured organism (39%). Fourteen patients (16%) were deemed emergent and underwent surgery within 24 h of review. A total of five patients died within their hospital stay postoperatively. Variables significantly associated with mortality on univariate analysis were intravenous drug use, emergent surgery, perioperative dialysis, perioperative inotropes, cardiopulmonary bypass time and cross clamp time. Only CBP time was significantly associated with mortality on multivariate analysis. A total of 19 patients (21%) required hemodialysis after surgery, 10 patients sustained a postoperative stroke (11%), 11 patients developed a complete heart block post operatively (12%) and endocarditis recurred in 10 patients (11%). Conclusion Prolonged cardiopulmonary bypass times were significantly associated with mortality. This study is novel to report a lower mortality rate than previously quoted in the literature. We also report our findings of organisms, preoperative embolic phenomena and surgery in a Western Australian population. We recommend that all patients with endocarditis are discussed in multidisciplinary forum.